An inexact cost-risk balanced model for regional energy structure adjustment management and resources environmental effect analysis-a case study of Shandong province, China. (1st May 2017) - Xie, Y.L.; Xia, D.H.; Ji, L.; Zhou, W.N.; Huang, G.H.
Abstract: Energy structure adjustment is a significant way to resolve constrained resources and environment, improve the security of energy supply, and achieve sustainable development, which is a complicated itself but further challenged by existence of uncertainties. In this study, an inexact multistage stochastic cost-risk balanced programming model is developed for energy system management under considering the policies of coal-consumption control and pollutants emission reduction. The method is an integration of inexact multistage stochastic programming and a risk management tools from modern financial theory, and could tackle uncertainties described as interval values and probability distributions. The method could reflect energy system dynamic characteristic in a multi-period problem, and provide an effective linkage between conflicting economic cost and the system stability. The proposed method is applied to a real case of planning electric power structure adjustment in Shandong province, China, where the energy system is faced with lots of difficulties complexities in electric power structure adjustment. The impact of coal-consumption control level and pollutants emission reduction scenarios on energy system structure adjustment, and resources and environmental effect were compared and analyzed. The results are valuable for supporting the adjustment or justification of the existing power generation schemes of the complicated regional energy system. Highlights: Inexact cost-risk balanced model for energy system management. Coal-consumption control and pollutants emission reduction are considered. Energy structure adjustment schemes, and resources and environmental effect were analyzed. Uncertainties were reflected as discrete intervals and probability distributions.